Hand hygiene products and adverse skin reactions: A cross-sectional comparison between healthcare and non-healthcare workers of Bangladesh during COVID-19 pandemic. Issue 12 (December 2022) - Roy, Simanta; Iktidar, Mohammad Azmain; Saha, Aishik Dipta; Chowdhury, Sreshtha; Tabassum Hridi, Syeda Tasnim; Sayeem Tanvir, Syed Md.; Hossain Hawlader, Mohammad Delwer
Abstract: Background: The deadly COVID-19 pandemic has swept the globe since December 2019. Due to the significant risk of infection, frontline health workers had to use Personal Protective Equipment and hand hygiene products, to help prevent transmission of infection. The present study aims to compare the adverse skin responses between healthcare workers (HCW) and non-healthcare workers (NHCW). Materials and methods: A descriptive, cross-sectional study of HCW and NHCW throughout the country wa executed. A self-structured questionnaire was utilized to gather data from 404 HCWs and 826 NHCWs during a two-month period using multistage sampling. STATA (v16) was used to analyse the data. Results: 41.87% of the study participants experienced adverse skin reactions, which were more prevalent amongs HCW (65.10%) than NHCW (30.51%). The most frequently reported skin condition was skin dryness (34.39%), followed by skin peeling (11.71%). Users of alcohol-based hand sanitizers (ABHS) were more likely to get itch (8.13%), whereas soap water users were more likely to suffer from skin peeling (35.74%) and rash (7.46%). There was a significant (p < 0.001) association between occupation and adverse skin responses, with HCW being 3.5 times more likely to have adverse skin manifestations than NHCW. Conclusion: The research showed that healthcare workers were at a greater risk to developing skin reactions than the overall population with frequent use of hand hygiene measures being a significant risk factor. Abstract : Hand wash, Hand Hygiene, Skin problem, Skin Reaction, Sanitizer.